Linear porokeratosis with bone abnormalities treated with compounded topical 2% cholesterol/2% lovastatin ointment. Issue 1 (10th November 2020) - Blue, Elliot; Abbott, James; Bowen, Anneli; Cipriano, Sarah D.
Abstract: We describe a case of linear porokeratosis with associated bone resorption in a 17‐year‐old female with marked improvement after 2% cholesterol/2% lovastatin ointment application. Porokeratosis is a heterogenous group of keratinization disorders characterized by a cornoid lamella, consisting of focal dyskeratotic cells in the granular layer and columns of parakeratosis. The pathogenesis of porokeratosis is not fully elucidated; however, germline mutations have recently been identified in the mevalonate pathway which can lead to a buildup of metabolites that could play a role in dysmaturation. There has only been one prior report of an affected distal digit with underlying bone resorption in association with linear porokeratosis.